Lb1.7 Australian national surveillance of juvenile onset recurrent respiratory papillomatosis: declining incidence post quadrivalent hpv vaccination. (8th July 2017) - Novakovic,; Brotherton, J; Garland, Suzanne; Cheng, A; Booy, R; Walker, P; Berkowitz, R; Harrison, H; Black, R; Perry, C; Vijayasekaran, S; Wabnitz, D; et al.
Abstract : Introduction: To estimate and monitor national incidence of Juvenile onset Recurrent Respiratory Papillomatosis (JoRRP) in Australia following the extensive quadrivalent HPV vaccine catch up program (females aged 12–26 years in 2007–2009, which included women of child bearing age) and to assess demographics and risk factors of incident cases. Methods: The Australian Paediatric Surveillance Unit (APSU) undertakes surveillance of rare paediatric diseases by contacting practitioners monthly to report cases. We utilised this well established methodology to undertake prospective population based surveillance of JoRRP by enrolment in APSU of paediatric ENT surgeons, designing a JoRRP case reporting form, and offering clinicians HPV typing of incident cases. Surveillance commenced Oct 2011 and we report here findings for the five-year period to end 2016. Results: Using Australian Bureau of Statistics population estimates for children 0–15 years, the average annual incidence rate over the period was 0.12 per 1 00 000. The largest number of cases was reported in the first year, with a decreasing frequency each year thereafter. The rate declined from 0.3 per 1 00 000 in 2012 to 0.04 per 1 00 000 in 2016. Among incident cases, no mothers had been vaccinated prior to pregnancy, 20% had a past history of genital warts, 60% of cases were male, and 60% were first born. The majority were born by vaginal delivery. Four incident cases were genotyped; all were positive for HPV6 (n=1) or HPV11 (n=3). Conclusion: To our knowledge this is the first report internationally documenting a decline in JoRRP incidence in a population of children following the introduction of a quadrivalent HPV vaccination program. Support : : I Professor Suzanne Garland, have received Grants to my institution from Commonwealth Department of Health for HPV genoprevalance surveillance post vaccination, Merck and GSK (GlaxoSmithKline) to perform phase 3 clinical vaccine trials: Merck to evaluate HPV in RRP post vaccination programme, CSL for HPV in cervical cancer study, and VCA (Victoria Cancer Agency) for a study on effectiveness of public health HPV vaccine study plus a study on associations of early onset cancers. I have received speaking fees from MSD and SPMSD for work performed in my personal time. Merck paid for travel and accommodation to present at HPV Advisory board meetings.